El índice cuantitativo de calidad web como instrumento objetivo de medición de la calidad de sitios web corporativos - Óscar R. González López; Tomás M. Ba\~negil Palacios; María Buenadicha Mateos (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2013)
– In the current economic crisis accurate assessment of the efficiency of the online strategy implemented by companies is a crucial issue. This paper proposes a number of indicators for the evaluation of the websites of companies all over the world. Our research examines the manual and automatic evaluation of a series of objective variables concerning website. To obtain the indicators we applied a factor analysis to the relevant variables. The Quantitative Web Quality Index is a versatile tool that permit us to compare any kind of organizations and detect the strong and weak points of the company's website.
Keywords: M15; 330; Website evaluation; Website quality; Website analysis; E-strategy